Flora and ulysses eaudiobook The illuminated adventures. - DiCamillo, Kate (Listening Library, 2013)
Soon to be an original movie on Disney+. The beloved 2014 Newbery Medal winner by former National Ambassador for Young People’s Literature Kate DiCamillo.   Holy unanticipated occurrences!   It begins, as the best superhero stories do, with a tragic accident that has unexpected consequences. The squirrel never saw the vacuum cleaner coming, but self-described cynic Flora Belle Buckman, who has read every issue of the comic book  Terrible Things Can Happen to You!,  is the just the right person to step in and save him. What neither can predict is that Ulysses (the squirrel) has been born anew, with powers of strength, flight, and misspelled poetry—and that Flora will be changed too, as she discovers the possibility of hope and the promise of a capacious heart.   From #1  New York Times  best-selling author Kate DiCamillo comes a laugh-out-loud story filled with eccentric, endearing characters.